Penggunaan Media Powerpoint Pada Pembelajaran Tematik di SD Muhammadiyah 1 Krian - Lucia Damasanti; Ermawati Zulikhatin Nuroh (Universitas Muhammadiyah Ponorogo, 2023)
Education is the basis for advancing a Country. In order to achieve a successful education system, therefore educators are expected to be able to improve the quality of educators who are able to educate by using various methods, and strategies and also present innovations prioritizing the use of technology. A problem found in the research is the thematic learning process, students seem to lack enthusiasm and do not pay attention to the teacher in following the learning process. In an era that is increasingly advanced in civilization, it also has an effect on the development of a field, including in the field of education. The existence of learning support media by utilizing technological advances will facilitate students in the learning process. One of the learning media used is power point learning media. The selection of the right learning media will have a good effect on student learning results, including thematic learning. The purpose of the research was to witness the use of digital learning media with the help of power points in thematic learning and to find out the student's response to the use of thematic learning media in grade 4 of SD Muhammadiyah 1 Krian. The research method used is qualitative, which is an elaboration method that describes a phenomenon that occurs in the field in a real way and as it is. Data collection instruments were carried out, including observations, interviews, and documentation at SD Muhammadiyah 1 Krian. The results of the research analysis that has been carried out refer to 4 aspects. As for the use of PowerPoint media in thematic subjects at SD Muhammadiyah Krian, it can be concluded in its implementation, the use of PowerPoint media in thematic learning at SD Muhammadiyah 1 Krian can attract and increase student motivation n in the learning delivered. With the use of PowerPoint learning media, the results of the assessment of student thematic learning above KKM